2017
DOI: 10.1002/term.2486
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of gel‐encapsulated adipose derived stem cells: Biochemical cues for in vivo peripheral nerve repair

Abstract: Adipose-derived stem cells (ASC) are becoming one of the most exploited cells in peripheral nerve repair. They are fast-growing and able to protect neurons from apoptosis; they can reduce postinjury latency and the risk of muscle atrophy. This study evaluates laminin-loaded fibrin gel as an ASC-carrying scaffold for nerve repair. In vitro, ASC retained their proliferative activity but showed significant increase in proliferation rate when encapsulated in gels with low laminin concentrations (i.e., 1 μg/mL). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…ASCs were harvested from Sprague–Dawley rats (Janvier, France) as described earlier(de Luca et al, ) and maintained in Modified Eagle Medium (α‐MEM; Invitrogen, UK) containing 1% (v/v) streptomycin/penicillin solution and 10% (v/v) FBS. ASCs were differentiated at early passages, i.e., 4–6.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ASCs were harvested from Sprague–Dawley rats (Janvier, France) as described earlier(de Luca et al, ) and maintained in Modified Eagle Medium (α‐MEM; Invitrogen, UK) containing 1% (v/v) streptomycin/penicillin solution and 10% (v/v) FBS. ASCs were differentiated at early passages, i.e., 4–6.…”
Section: Methodsmentioning
confidence: 99%
“…Suboptimal outcome is attributed to axonal degeneration, fibrotic scar formation, and neuromas at the site of injury (Ngeow, ). Previous research has focused on the different cellular and structural components of the regenerating nich e and managed to improve peripheral nerve regeneration through axonal guidance with neural conduits (Zhang et al, ; Wang et al, ), growth factor delivery (Madduri et al, ), cell therapy hydrogels (Masand et al, ) and extracellular matrix molecules (de Luca et al, ; de Luca et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Мезенхімальні стовбурові клітини кісткового мозку (МСК-КМ) позбавлені таких недоліків, як туморогенність і морально-етичні проблеми, можуть бути отримані за допомогою пункції кісткового мозку, а в спеціальних умовах культивування можуть диференціюватися у нейрони, астроцити та шванівські клітини [96,97]. Багато дослідників показали, що використання МСК-КМ сумісно з матриксами для тубажу нерва чи ацелюлярними нервами дає кращі результати ніж використання самих порожнистих матриксів без МСК-КМ [74, 98-100], інші, що позитивний ефект від застосування МСК-КМ гірший ніж при використанні культивованих шванівських клітин [101], але більшість погоджуються з думкою, що ефект приблизно однаковий [102,103].…”
Section: джерела і види стовбурових клітин для відновлення периферичнunclassified
“…For instance, silicone (polydimethylsiloxane) tubes, encapsulating adipose-derived stem cells and inserted between nerve stumps, reportedly induced regeneration in rat sciatic nerves. 18 A bioabsorbable polyglycolic acid tube filled with collagen sponge enabled the reconnection of canine peroneal nerves. 19 Such tubes have also been investigated in clinical studies and were reported to improve functional nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%